Aerobic capacity, physical activity and pain in adult victims of moderate to severe burns after discharge (Acta Scientiarum. Health Sciences, 2017)
Burns cause different impacts on the individual life. Many are the problems faced by survivors, such as hypermetabolism that may persist years after the event. The aim was to assess aerobic capacity, level of physical activity and pain in adult burn victims after hospital discharge. This is a descriptive, cross-sectional study. Participants (n = 60) were adult victims of moderate to severe burns, evaluated by six-minute walk test (6MWT), Pain Scale and International Physical Activity Questionnaire (IPAQ). We applied Student’s t-test for independent samples and Mann-Whitney test for comparisons between medium and large burned; Chi-square test to compare the level of physical activity. Large burned (73%) patients prevailed among the 60 participants; there was a statistically significant trend in the distance predicted between groups (p = 0.066), with no change in performance of the aerobic capacity. 60% reported physical activity practice at least three times a week: walking, cycling and soccer. As for the level of pain, 40% reported moderate to severe persistent pain, even after complete healing of wounds. Most participants showed aerobic capacity within the normal range, despite the high body mass index reported, they reported doing physical activities of moderate intensity.